Influence of winter rations and gains on subsequent pasture gains. - Pickett, A.G.; Weber, A.D. (Kansas Agricultural Experiment Station, 2012)
Many authorities and successful beef cattle producers have held the belief that the safest long-time beef production system was one that kept the producer in business 12 months of the year. This, of course, means wintering, grazing and under certain conditions, feeding some grain. In the past we have not been in a position here at the college to work out details of the various systems of beef production since experiment grazing land was not available. March 1, 1947 we gained possession of 1,143 acres of bluestem grass which will be used to develop the best systems of beef cattle production. Other problems dealing with grass utilization will also be studied.
Keywords: Beef; Winter rations; Gain; Pasture gains